Sinergi HR dan Teknologi dalam Membangun Organisasi Pembelajar: Jalan Menuju Pendidikan dan Bisnis Berkelanjutan - Ardhit Wiro Hartono; Viko Rachmatullah Putra; Mohammad Makhrisyafrisal; Junengsih (CV ODIS, 2025)
The rapid wave of digital transformation over the past two decades has compelled organizations across sectors—particularly in education and business—to adapt swiftly and strategically. In this context, Human Resource (HR) management can no longer function solely as an administrative support system; it must evolve into a strategic partner that fosters a culture of continuous learning while driving comprehensive technological integration. This study explores the synergy between HR and technology in building a learning organization as a foundation for sustainable education and business in the digital era. Employing a qualitative descriptive approach, this research investigates best practices from five institutions—three higher education institutions and two national technology-based companies—that have adopted digital HR systems and adaptive learning cultures. Data were collected through in-depth interviews, field observations, and document analysis. The findings reveal that the integration of digital HR systems significantly enhances employees’ digital literacy, accelerates organizational learning processes, and creates participatory environments that uphold humanistic values such as empathy, collaboration, and innovation. This research aligns with the broader dissemination theme and shows that HR-tech synergy is not only a key internal transformation strategy but also a bridge between knowledge, humanity, and social responsibility in the 21st century.